Operasi Pengangkatan Batu Kandung Kemih Pada Anjing Mini Pomeranian - Palestin Djazuli; Hana Cipka Pramudha Wardhani; Era Hari Mudji Restijono; Intan Permatasari Hermawan; Kurnia Desiandura Desiandura; Victor Yulius Sulangi (Acta VETERINARIA Indonesiana, 2022)
Urolithiasis is a common disease affecting the urinary tract, including the bladder. This disease is characterized by the presence of formed stones in the urinary tract. A five years old female mini Pomeranian dog with a bodyweight of 5 kg was complaint with anorexia, oliguria, and hematuria. The result of the physical examination by palpation is a distended abdominal area. The supporting examination was carried out in the form of an ultrasound examination (USG). The results of ultrasound examination showed a hyperechoic colored foreign object with an oval shape with smooth edges at the base of the bladder and resulted in acoustic shadowing at the bottom of the calculi. In addition, the hematology analysis exhibited granulocytosis, leukocytosis, and increase Alkaline Phosphatase (ALKP). The dog was diagnosed with urolithiasis with the prognosis of Fausta. The cystotomy surgery was performed to remove the bladder stone. Postoperative therapy is Cefixime, Cystaid®, Fibumin®, dan Coatex®. The healing showed good progress in 5 days.